High-Resolution Genotyping of Campylobacter Strains Isolated from Poultry and Humans with Amplified Fragment Length Polymorphism Fingerprinting - Duim, Birgitta (American Society for Microbiology, 1999)
For epidemiological studies of Campylobacter infections, molecular typing methods that can differentiate campylobacters at the strain level are needed. In this study we used a recently developed genotyping method, amplified fragment length polymorphism (AFLP), which is based on selective amplification of restriction fragments of chromosomal DNA, for genetic typing of Campylobacter jejuni and Campylobacter coli strains derived from humans and poultry. We developed an automated AFLP fingerprinting method in which restriction endonucleases HindIII and HhaI were used in combination with one set of selective PCR primers. This method resulted in evenly distributed band patterns for amplified fragments ranging from 50 to 500 bp long. The discriminatory power of AFLP was assessed with a C. jejuni strain, an isogenic flagellin mutant, and distinct C. jejuni strains having known pulsed-field gel electrophoresis and fla PCR-restriction fragment length polymorphism genotypes. Unrelated C. jejuni strains produced heterogeneous patterns, whereas genetically related strains produced similar AFLP patterns. Twenty-five Campylobacter strains obtained from poultry farms in The Netherlands grouped in three C. jejuni clusters that were separate from a C. coli cluster. The band patterns of 10 C. jejuni strains isolated from humans were heterogeneous, and most of these strains grouped with poultry strains. Our results show that AFLP analysis can distinguish genetically unrelated strains from genetically related strains of Campylobacter species. However, desirable genetically related strains can be differentiated by using other genotyping methods. We concluded that automated AFLP analysis is an attractive tool which can be used as a primary method for subtyping large numbers of Campylobacter strains and is extremely useful for epidemiological investigations.